Understanding QRPs and Blatant Misconduct in Applied Linguistics Research: A Book Review of Addressing Questionable Research Practices in Applied Linguistics: A Practical Guide - ALIMUDDIN, Andi Haeriati; HASYIM, Irmawaty (Research and Innovation in Applied Linguistics, 2024)
his book explores the ethical gray area of Questionable Research Practices (QRPs), including its similarities and differences (Butler et al., 2017; Ravn & Sørensen, 2021). It lies between responsible research conduct and clear misconduct like falsification, fabrication, plagiarism. It helps Applied Linguistics (henceforth AL) researchers to carry out ethical research which addresses the ambiguity and debate surrounding certain practices, such as data sharing and outlier management. They are often not well covered in traditional research ethics training. There is a need for AL researcher to identify the good, the bad, and the ugly in the research practices (Banks et al., 2016). To enhance understanding and ethical decision-making, the book provides a taxonomy of 58 QRPs, lesson plans, suggested readings, and discussion scenarios for use in research methods courses and workshops.